Cuidados de enfermería en pacientes con diabetes que acuden al dispensario médico del seguro social campesino Bella Aurora, cantón Mocache, provincia de los Ríos, primer semestre del año 2013 - Rizzo Murillo, Jacqueline Maribel (2013)
Diabetes is ravaging Latin America, by reducing both the quality and life expectancy of millions of its inhabitants. About 20 million people currently suffer from this disease in the region , and that figure is expected to rise to 40 million by 2025 . Never before has done this type of research so I considered it appropriate to study the " Nursing care in patients with diabetes attending the medical clinic of the rural social security Mocache Bella Aurora Canton province of Los Ríos , first half year 2013. " The objective of this paper is to investigate nursing care plan applies to diabetic patients attending the medical clinic of rural social insurance Bella Aurora . The following hypothesis remains With the plan of nursing care in patients with diabetes attending the medical clinic of the rural social security Bella Aurora severe disabilities will decrease . ? Reaching the following conclusions diabetic patients dispensary rural social security Bella Aurora , Mocache Canton province of Los Rios . 94% do not know the dietary habits to control their disease in an efficient manner , but if they go to that clinic per quarter. At the end of this research we performed reflection of some events as the nursing staff of the medical clinic of the rural social security Bella Aurora , Canton Mocache province of Los Rios , you must make a plan of care in patients with diabetes, which must be carried by the patient , it must be monitored, and reprogrammed monitored by the nurse in order to avoid further complications